2016
DOI: 10.1099/jgv.0.000461
|View full text |Cite
|
Sign up to set email alerts
|

Highly diverse posaviruses in swine faeces are aquatic in origin

Abstract: Posaviruses are a group of highly divergent viruses identified in swine faeces that are distantly related to other members of the order Picornavirales. Eighteen posavirus genomes were assembled from 10 out of 25 (40 %) faecal-swab pools collected from healthy adult swine. Phylogenetic analysis of the conserved RNA-dependent RNA polymerase (Pol) domain found that posaviruses form a large, highly diverse, monophyletic clade, which includes similar viruses identified in human (husavirus) and fish (fisavirus) faec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The largest and most coherent of the Branch 2 clades includes the cornerstone of the picornavirus supergroup, the ~826 viruses-strong order Picornavirales (56), expanded with caliciviruses, solinviviruses and a multitude of unclassified viruses infecting invertebrates, vertebrates, fungi, protists and undefined hosts (for viruses discovered by metaviromics) (Figure 3) (11, 14, 17, 57-59). The second largest, deep-branching clade consists of two lineages that include, respectively, +RNA and dsRNA viruses (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The largest and most coherent of the Branch 2 clades includes the cornerstone of the picornavirus supergroup, the ~826 viruses-strong order Picornavirales (56), expanded with caliciviruses, solinviviruses and a multitude of unclassified viruses infecting invertebrates, vertebrates, fungi, protists and undefined hosts (for viruses discovered by metaviromics) (Figure 3) (11, 14, 17, 57-59). The second largest, deep-branching clade consists of two lineages that include, respectively, +RNA and dsRNA viruses (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The largest and most coherent of the branch 2 clades includes the cornerstone of the picornavirus supergroup, the ϳ826 viruses-strong order Picornavirales (56), expanded with caliciviruses, solinviviruses, and a multitude of unclassified viruses infecting invertebrates, vertebrates, fungi, protists, and undefined hosts (for viruses discovered by metaviromics) ( Fig. 3) (11,14,17,(57)(58)(59). The second largest, deep-branching clade consists of two lineages that include, respectively, ϩRNA and dsRNA viruses ( Fig.…”
Section: Evolution Of the 5 Major Branches Of Rna Viruses And Reconstmentioning
confidence: 99%
“…Genomic organization is variable with a single polyprotein expressed in all orders except Dicistroviridae where structural and non-structural protein genes are expressed from separate transcripts [ 29 ]. Recently, some highly divergent members of the Picornavirales order have been discovered, including porcine-stool-associated RNA viruses (posaviruses) in the feces of pigs [ 30 32 ], fish-stool-associated RNA virus (fisavirus) in the intestinal content of a healthy carp [ 33 ], and human-stool-associated virus (husavirus) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis based on the amino acid sequence of RdRp indicated that these genomes clustered together with those of posaviruses from pig feces and the transcriptome of an Ascaris suum transcriptome (Fig. 5 b) [ 32 ]. Since an Ascaris suum transcriptome sequence was also grouped into this cluster, pansaviruses may not actually infect the intestinal cells of the giant panda but a nematode species in the gut of these animals, a potential source supported by the clinical record that the diseased giant panda contained ascarids in its intestine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation